The effect of Artemia fed with different diets on the growth and survival of Penaeus Monodon Fabricius Postlarvae - Yashiro, Renu. (1982)
Penaeus monodon postlarvae (P₁) with an average weight of 0.4 mg were stocked at the rate of 10 individuals per liter in a 250-liter conical fiberglass tanks filled with 150 liters of sand-gravel filtered seawater with a salinity range from 32.0 to 33.0 ppt, temperature from 26.5⁰ C to 28.7⁰ C and pH from 8.1 to 8.3. They were fed in excess with finely ground cooked mussel meat and live preadult Artemia (fed with wheat flour, rice bran or milled rice extracts) for 20 days. The postlarvae fed with cooked mussel meat had significantly lower weight gain (P< 0.05) than those fed with Artemia. No significant differences were found among the weight gains of shrimp fed with Artemia although slightly higher weight gains was observed with the postlarvae that received Artemia fed with milled rice extract. The survival rate was highest for shrimp fed with cooked mussel meat. This was significantly higher than those shrimp fed with Artemia except that of shrimp fed with Artemia that received milled rice extract. The total body lipid contents of the post-experimental shrimp were higher than that of the pre-experimental shrimp. Fatty acid composition of shrimp was generally related to the fatty acid pattern of the diets. Shrimp fed with cooked mussel meat had fatty acid profile similar to that of the pre-experimental shrimp. Among four treatments, the ration of ⟒3 / ⟒ 6 fatty acids was highest (2.17) in shrimp fed cooked mussel meat which had a ratio of 4.06. The other three treatments ratio were 1.17, 0.99 and 0.60 for shrimp fed with Artemia that received milled rice, wheat flour and rice bran extracts, respectively.
Thesis (MS Fisheries - Aquaculture). -- [Diliman, QC] : UP System, April 1982.